2020
DOI: 10.1186/s10086-020-01913-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of processing parameters for the manufacturing of jute stick binderless particleboard

Abstract: This study investigated the effects of processing parameters, namely particle mixing ratios, press temperatures, and time for the manufacturing of jute stick binderless particleboard (JBPB). Different ratios of fine and coarse particles, press temperature (160 to 240 °C) and press time (4 to 10 min) were used for JBPB fabrication with a target density of 0.9 g/cm3. The dimensional stability and mechanical properties of JBPB were determined according to Japanese Industrial Standard JIS A 5908 (2003). The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…Since lignins are hydrophobic by nature, with non-polar hydrocarbon chains and aromatic rings that prevent water from entering (which can cause swelling in the cell wall), they cause an increased resistance to water penetration (Mancera et al 2011;Nasir et al 2019). Another aspect to consider is the reduction in the amount of hydroxyl groups that are easily accessible by water, due to hemicellulose degradation (Kurokochi and Sato 2020;Nitu et al 2020;Song et al 2020), which was also confirmed by the FTIR spectra of BBP in the present study. This view is also in line with the study by Gao et al (2011), which asserted that a low TS value is associated with the polymerization, cross-linking, and/or other transformations of hydrophilic components of bark into a hydrophobic product during hot pressing under high temperature for a sufficient period.…”
Section: Bioresourcescomsupporting
confidence: 75%
See 1 more Smart Citation
“…Since lignins are hydrophobic by nature, with non-polar hydrocarbon chains and aromatic rings that prevent water from entering (which can cause swelling in the cell wall), they cause an increased resistance to water penetration (Mancera et al 2011;Nasir et al 2019). Another aspect to consider is the reduction in the amount of hydroxyl groups that are easily accessible by water, due to hemicellulose degradation (Kurokochi and Sato 2020;Nitu et al 2020;Song et al 2020), which was also confirmed by the FTIR spectra of BBP in the present study. This view is also in line with the study by Gao et al (2011), which asserted that a low TS value is associated with the polymerization, cross-linking, and/or other transformations of hydrophilic components of bark into a hydrophobic product during hot pressing under high temperature for a sufficient period.…”
Section: Bioresourcescomsupporting
confidence: 75%
“…The material also emitted a distinctive odor. Similar results were also noticeable in the binderless boards made using the following raw materials: bagasse (Panyakaew and Fotios 2011), palm oil trunk (Boon et al 2013), unripe coconut husk (Araújo Junior et al 2018), wheat straw (Wang et al 2019), soybean straw (Song et al 2020), jute stick (Nitu et al 2020), and densified wood (Shi et al 2020); this could be the result of the modification of the chemical components that occurs during the heat treatment (Panyakaew and Fotios 2011;Wang et al 2019). The presence of hemicellulose degradation and extractive movement may be the cause of the darkening of the color (Shi et al 2020).…”
Section: Resultssupporting
confidence: 55%
“…The strength of the PB at tension perpendicular to the plan depends on a number of factors, which include: size and shape of particles, particle size distribution, type of adhesive, material of particles, temperature and duration of pressing, degree of compaction [1,2,5]. In current work, we focus only on the influence of two factors, namely the size and shape of the particles.…”
Section: Figure 7: Geometric Particle Modelmentioning
confidence: 99%
“…The PBs production increases over time. New types of PB appear [1,2]. Contemporary PB technologies [3,4,5] allow the rational use of large volumes of low-quality wood (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…To fabricate the diversified jute products, it can be blended with other fibers such as cotton, wool, polyester, etc., in different ratios to improve its inherent properties. Combining jute and cotton yarns to several ratios of 30:70, 40:60, and 50:50 are designed by other researchers with a very distinctive approach [ 20 , 21 , 22 ]. To confirm its acceptance as a diversified product and gain its manufacturers' confidence and raise its commercial value, some significant criteria like physical and thermo-physiological comfort, dyeability, wettability, etc., are also needed to satisfy the product's outer bright appearance.…”
Section: Introductionmentioning
confidence: 99%